Analysis Analysis of the Potential and Development Strategies for Swines Farming in Dairi Regency - perdhinan sianipar; G.A.W Siregar; R.E Mirwandhono; A.N Sari (Jurnal Peternakan Integratif, 2025)
One of the regency that has the potential to develop swines in North Sumatera Province is Dairy. The purpose of this study was to determine the potential of livestock resources, the area and carrying capacity of swines and alternative strategies that were effective in developing swines in Dairi Regency. This research was conducted in June- August 2023 by applying the stratified sampling method to all districts in Dairi Regency and utilizing purposive sampling to select districts with the highest population, namely Silima Pungga-pungga District, districts with moderate population, namely Siempat Nempu District and district with low population, namely Lae Parira District. Samplig is done using the method of determining the quota of 30 respondents in each district. Analysis of the data carried out is descriptive analysis, LQ, livestock density, feed concentration index, carrying capacity of agricultural and plantation waste, and SWOT analysis. Based on the results, dairy Regency has the potential to develop swines. The livestock density is still low and has the potential to be increased. The production of dry agricultural and plantation waste is 859.881,18 tons and 8.431,51 ton. DDLP and IDDLP are classified as high, while IKP is not evenly distributed. Respectively the capacity based on the production of dry agricultural waste is 755.054,504 adult swines. The appropriate and prioritized strategy is SO strategy. Dairi Regency is suitable for swines farming development.